2022
DOI: 10.1039/d1cp04657h
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow lattice thermal conductivity at room temperature in 2D KCuSe from first-principles calculations

Abstract: Ultralow lattice thermal conductivity is crucial to achieve a high thermoelectric figure of merit for thermoelectric applications. In this work, using the first-principles and phonon Boltzmann transport theory, we investigate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…On the whole, the lattice thermal conductivity decreases with increasing temperature, following the general law of κ l ∝ 1/ T , indicating that the U-process dominates the three-phonon scattering. 52 At 300 K, the κ l values in the x - and y -directions are 14.61 and 15.43 W m −1 K −1 , respectively, which are much smaller than those of MoS 2 /WS 2 (68.44 W m −1 K −1 ) 53 and WSe 2 /SnS 2 vdWHs (22.69 W m −1 K −1 ). 22 It is intriguing that the κ l of GaSe/SnS 2 exhibits a weak anisotropy, which does not appear in its constituents.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…On the whole, the lattice thermal conductivity decreases with increasing temperature, following the general law of κ l ∝ 1/ T , indicating that the U-process dominates the three-phonon scattering. 52 At 300 K, the κ l values in the x - and y -directions are 14.61 and 15.43 W m −1 K −1 , respectively, which are much smaller than those of MoS 2 /WS 2 (68.44 W m −1 K −1 ) 53 and WSe 2 /SnS 2 vdWHs (22.69 W m −1 K −1 ). 22 It is intriguing that the κ l of GaSe/SnS 2 exhibits a weak anisotropy, which does not appear in its constituents.…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, we only focus on these eight phonon branches (phonon frequencies around 0–4.74 THz). The lattice thermal conductivity can be expressed as 52 where V is the volume of the primitive cell, and C , τ and ν are the specific heat, phonon relaxation time and phonon group velocity, respectively. λ denotes each phonon mode, and α is the Cartesian direction.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies have indicated that the Coulomb interaction is important to guarantee the dynamical stability for some d or f electron systems such as TiS 2 and U 3 Si 2 [23,24], and thus the Coulomb interactions are considered by using the effective Hubbard U values of 7 eV and 4 eV for 5d electrons of Tl atom and 3d electrons of Cu atom, respectively, because the Tl 4f electrons are far below the Fermi level. These U values have been used in some systems including Tl and Cu atoms such as Tl 3 TaS 4 , UTl 3 , KCuSe and CuO [25][26][27][28]. The kpoint meshes of 12 × 12 × 6 and 12 × 12 × 1 are used for bulk and monolayer TlCuSe, respectively.…”
Section: Methodsmentioning
confidence: 99%